2x-5=4x+13

Simple and best practice solution for 2x-5=4x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5=4x+13 equation:


Simplifying
2x + -5 = 4x + 13

Reorder the terms:
-5 + 2x = 4x + 13

Reorder the terms:
-5 + 2x = 13 + 4x

Solving
-5 + 2x = 13 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-5 + 2x + -4x = 13 + 4x + -4x

Combine like terms: 2x + -4x = -2x
-5 + -2x = 13 + 4x + -4x

Combine like terms: 4x + -4x = 0
-5 + -2x = 13 + 0
-5 + -2x = 13

Add '5' to each side of the equation.
-5 + 5 + -2x = 13 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = 13 + 5
-2x = 13 + 5

Combine like terms: 13 + 5 = 18
-2x = 18

Divide each side by '-2'.
x = -9

Simplifying
x = -9

See similar equations:

| 8+2p-5=6p+8-3p | | -3x+12x= | | 7a+10a= | | 13c^2-52= | | 3(4x-3)=51 | | 4p^2+164p+81= | | (t+3)(t-4)=5 | | 100x^2+1400x+4500=0 | | x-121=4(x-5) | | -3x^2-31x+22=0 | | 10x+3=6-2x+3 | | n*9+4=58 | | 9m^3-7m^4+8m^2= | | 6x-3*6x+3=57 | | -5x^2=-3x | | -3a^10+9a^5+6a^15= | | .25x^2-2y=5 | | .25h+9=.75h-7 | | 3t^2-5t-2t^4= | | 4x^2-42x-22=0 | | 21x^4+18x^2+36x^3= | | 3x^2+12x+20=8 | | -2x^2-x^2-30x-72=0 | | 8x-23=2x+37 | | (3x+5)(7x^2-2x+1)= | | 5+4x=3x^2 | | -2x^2-12x-18=0 | | 10x^2-50x+40=0 | | (a-4)(6a^2+10a-3)= | | 3x^2=4x+5 | | X^2+2-2lnx=0 | | -5x^2-9x=0 |

Equations solver categories